Complete genome sequences of 30 bacterial species from a synthetic community - Hogle, Shane L; Tamminen, Manu; Hiltunen, Teppo (American Society for Microbiology, 2025)
We present complete genome sequences from 30 bacterial species that can be used to construct defined synthetic communities that stably form in the laboratory under controlled conditions.